Olfactory Dysfunction is not a Determinant Of Patient‐Reported Chronic Rhinosinusitis Disease Control. (10th December 2020) - McCann, Adam C.; Trope, Michal; Walker, Victoria L.; Kavoosi, Tazheh A.; Speth, Marlene M.; Gengler, Isabelle; Phillips, Katie M.; Sedaghat, Ahmad R.
Abstract : Objectives/Hypothesis: As a cardinal symptom of chronic rhinosinusitis (CRS), hyposmia has been recommended to be assessed as a component of CRS disease control. Herein we determine the significance of hyposmia in CRS in the context of nasal obstruction and drainage symptoms. Study Design: Prospective, cross‐sectional Methods: Cross‐sectional study of 308 CRS patients (102 CRSwNP, 206 CRSsNP) without prior endoscopic sinus surgery. The burden of nasal obstruction and hyposmia were assessed using the corresponding item scores on the 22‐item Sinonasal Outcome Test (SNOT‐22). Burden of nasal discharge was assessed using the mean of "thick nasal discharge" and "thick post‐nasal discharge" SNOT‐22 item scores. Patients were all asked to rate their CRS symptom control as "not at all, " "a little, " "somewhat, " "very, " or "completely." Results: In CRSwNP, only 4.9% had a hyposmia score > 1 with nasal obstruction and drainage scores less than or equal to 1. In CRSsNP, only 1.9% had a hyposmia score > 1 with nasal obstruction and drainage scores less than or equal to 1. On univariate association, CRS symptom control was significantly associated with nasal obstruction, hyposmia, and drainage in both CRSwNP and CRSsNP ( P  < .05 in all cases). Using multivariable regression to account for all nasal symptoms, only nasal obstruction and nasal discharge scores (but not hyposmia) were significantly associated with CRS symptom control. Conclusions: Hyposmia rarely occurs without nasal obstruction or nasal drainage, and may therefore be redundant to assess for CRS disease control. Moreover, hyposmia was not associated with patient‐reported CRS symptom control when accounting for the burden of nasal obstruction and drainage. Level of Evidence: 3 Laryngoscope, 131:E2116–E2120, 2021